Deep ice core drilling to a depth of 3035.22 m at Dome Fuji, Antarctica in 2001–07. Issue 85 (22nd September 2021) - Motoyama, Hideaki; Takahashi, Akiyoshi; Tanaka, Yoichi; Shinbori, Kunio; Miyahara, Morihiro; Yoshimoto, Takayasu; Fujii, Yoshiyuki; Furusaki, Atsushi; Azuma, Nobuhiko; Ozawa, Yukio; Kobayashi, Akio; Yoshise, Yasushi
Abstract: The Japanese second deep ice coring project was carried out at Dome Fuji, Antarctica. Following the drilling of the pilot hole in 2001, deep ice core drilling led by the Japanese Antarctic Research Expedition (JARE) was conducted over four austral summer seasons, beginning with the 2003/04 season and reached a depth of 3035.22 m near the bedrock in January 2007. The new drill was designed and developed with the goals of (1) solving the problems encountered during the first JARE deep coring drill and (2) achieving more efficient drilling. In particular, the maximum core length that can be drilled at one time was increased from 2.30 m to 3.84 m and the chip storage efficiency was enhanced by a special pipe with many small holes. This paper gives an outline of the improved drilling system, the progress of drilling and various drilling data.